Islam in a post-secular society religion, secularity and the antagonism of recalcitrant faith - Byrd, Dustin J. (Studies in critical social sciences,, 2017)
Islam in the Post-Secular Society: Religion, Secularity and the Antagonism of Recalcitrant Faith critically examines the unique challenges facing Muslims in Europe and North America. From the philosophical perspective of the Frankfurt School's critical theory, this book attempts not only to diagnose the current problems stemming from a marginalization of Islam in the secular West, but also to offer a proposal for a Habermasian discourse between the religious and the secular. By highlighting historical examples of Islamic and western rapprochement, and rejecting the 'clash of civilization' thesis, the author attempts to find a 'common language' between the religious and the secular, which can serve as a vehicle for a future reconciliation.